Pèlerins français en route pour Rome en 1600 - Stéphane Gomis (Belgeo)
In 1600, the universal jubilee in Rome sees large crowds of pilgrims, in which the subjects of the King of France are fairly well represented. In this context, the diary kept during the pilgrimage that year by sixteen priests from the region of Dreux in the French diocese of Chartres, is a document rich in information. The author of this booklet is not a member of the clergy. Indeed, he is the seventeenth pilgrim, parent of one of the clerics, Laurent Barbereau, a notary by trade. This originality leads to question this kind of writing produced from the first-person writing, the actors directed by our writer as well as the nature of their spiritual quest. Finally, it is important to question the organization and conduct of such a journey. In total, guide, fact sheets, account book, the main purpose of these sheets is, above all, to be useful.